Integral representation of the scalar propagators on the de Sitter expanding universe - Ion I. Cotăescu; Ion Cotăescu (European Physical Journal C: Particles and Fields, 2019)
Abstract A new type of integral representation is proposed for the propagators of the massive Klein–Gordon field minimally coupled to gravity of the de Sitter expanding universe. This representation encapsulates the effects of the Heaviside step functions of the Feynman propagators, making possible for the first time the calculation of Feynman diagrams involving scalar particles on this background. In order to convince the reader, a simple example is given outlining as a premiere the amplitudes in the second order of perturbations of the Compton effect in the de Sitter scalar quantum electrodynamics.